STRUKTUR KOMUNITAS MIKROALGA DI EKOSISTEM RAWA GAMBUT CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) - Indriani Indriani; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The potential source of diversity in the Riau peat swamp ecosystem can still be explored. This research was conducted to know the microalgae community structure from the peat swamp ecosystem of giam siak kecil-bukit batu biosphere reserve (CBGSK-BB) and produce a design of work sheet of students, in July-September 2018. The research method was field data collection with explorative research, while microalgae data collection used the survey method. Sampling of peat water from 3 stations in Temiang Village, CBGSK-BB transition area. Measurement of physical and chemical parameters of the waters, namely light intensity, temperature, and pH. Observation of samples in the Biology Education Laboratory, FKIP University of Riau, for calculating biological parameters (abundance, diversity index, and evenness index). Integrated research data for teaching materials consisted of student worksheet with ADDIE, model, and Analysis. The highest percentage of microalgae species composition was from Chlorophyceae class at 88.63%. The abundance of microalgae in the waters between 55,660 ind/L to 701,800 ind/L, in the classification of mesotrophic waters (medium fertility). The lowest evenness index at Station II worth 0.13 shows that the distribution of individuals is not equal, dominates the dominance of one species, compared to other stations more than 1. The microalgae diversity index reaches 0.18-1.81, the microalgae community changes in the Peat swamp ecosystem of the Village Temiang is at a low to moderate level. The results of the study were developed as a material enrichment in the design of the student worksheet for protista material 1st grade senior high school.Key Words: Mikcroalgae, Peat, Community Structure